Efikasi Caring Mahasiswa Program Studi Pendidikan Profesi Ners - Gusni Fitri; Rahma Yulis (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Caring is an important part of nursing where Caring is the basis, but it is a problem that often occurs in the field, research found that recurring problems in hospitals are that the lack of caring and communication of nurses to patients and the little time nurses spend with patients. Caring efficacy is the confidence or ability of nurses to behave attentively and build good relationships with patients. Nursing professional students as prospective professional nurses have high caring efficacy so they can apply caring well when providing nursing care to patients. Nurses who cannot carry out caring behaviors well can also be caused by low self-efficacy. This study aims to see the caring efficacy of students in the nursing professional education study program where they are prospective professional nurses. The method in this study is descriptive with a total sampling technique of 32 respondents. The results showed that most of the respondents were female, aged 22 years and the caring efficacy of students in the nursing professional education study program was mostly moderate. It is hoped that students' caring efficacy will increase with increasing experience so that they can be more optimal in providing nursing services.